"Touching" services: tangible objects create an emotional connection to services even before their first use - Nora Nägele; Benjamin von Walter; Philipp Scharfenberger; Daniel Wentzel (Business Research, 2020)
Although research suggests that physical elements of the servicescape play an important role in the service process, there is little research on the impact of tangible objects that companies give to consumers such as membership cards, pens, mugs, or fashion articles. Drawing on research about embodied cognition, this paper investigates how and under which conditions the provision of tangible service objects affects consumers. Three experimental studies were conducted, in which participants received different objects they could either touch or just see. These studies indicate that touching a service object metaphorically translates into a perceived mental connection towards the service. More specifically, physically connecting to a service object leads to a stronger psychological connection to the corresponding service, which, in turn, increases behavioral intentions. The results also demonstrate that providing a tangible object only has an impact when the object is of high aesthetic appeal. These findings suggest that providing tangible service objects is an effective way for service providers to build an emotional connection with potential customers and to strengthen the emotional connections of existing customers.
Keywords: 650; Service objects; Embodied cognition; Servicescape; Corporate gifts; Touch; Service experience